ESTIMATION OF ELECTRICAL PROPERTIES OF ROCK FOR GRANULAR PORE MODELS AND CRACKS USING FINITE ELEMENT METHODS - BISRI MUSTOFA (NIM : 20215058), MUHAMMAD
Electrical conductivity is a powerful parameter in determining type of reservoirs which depends on pore space geometry. Studies on this topic have been done by many researchers, e.g. by examining the relationship of electrical conductivity with a pore radius, grain shape, and many more microstructure parameters. Here, we reviewing this relationship, with conducted Granular pore models and crack models. Both are chosen to compare the change in electrical conductivity as a function of porosity and size. The model conducted by varying the value of porisity (i.e.: 0.05 to 0.35) and the size of sample size (323 - 1283 voxels). Models of fully saturated porous rocks used in this study consist of solid and fluid phase with electrical conductivity of 0.01 S/m and 0.2 S/m respectively. Electrical conductivity calculations are performed by computational techniques using finite element method (FEM) through energy approach, which has been compared in advance by analytical approach. Among the analytical approaches used to compare the numerical codes are series-parallel layers, the Browns equation, Keller-Mendellson, and Nguyens equation. Comparison has been done both for 2D and 3D models and the results show good agrement. Based on the calculation of the whole of model show that the value of electrical conductivity of fracture model greater than the other one, this becomes important when we will identify a rock sample.